2016
DOI: 10.18632/oncotarget.14185
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-associated macrophages promote prostate cancer migration through activation of the CCL22-CCR4 axis

Abstract: Previous studies have found that tumor-associated macrophages (TAMs) promote cancer progression. We previously reported that TAMs promote prostate cancer metastasis via activation of the CCL2–CCR2 axis. The CCR4 (receptor of CCL17 and CCL22) expression level in breast cancer was reported to be associated with lung metastasis. The aim of this study was to elucidate the role of CCR2 and CCR4 in prostate cancer progression. CCR2 and CCR4 were expressed in human prostate cancer cell lines and prostate cancer tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
102
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 106 publications
(107 citation statements)
references
References 30 publications
4
102
0
1
Order By: Relevance
“…Co‐cultures of SaOS‐2 cells and bone stromal cells with prostate cancer cells found that both cell types induced the migration of AR‐positive cancer cells. Bone tissue is rich in cytokines that are known to affect the behavior of cancer cells . CCL5 was consistently secreted by BDSC and BmetSC and, as previously shown, directly increased prostate cancer cell migration but not proliferation.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Co‐cultures of SaOS‐2 cells and bone stromal cells with prostate cancer cells found that both cell types induced the migration of AR‐positive cancer cells. Bone tissue is rich in cytokines that are known to affect the behavior of cancer cells . CCL5 was consistently secreted by BDSC and BmetSC and, as previously shown, directly increased prostate cancer cell migration but not proliferation.…”
Section: Discussionsupporting
confidence: 56%
“…For example, C‐C motif ligand 2 (CCL2) is present in the microenvironment of many cancers and upregulated in prostate cancer cells . We previously reported that bone stromal cells and SaOS‐2 osteoblast‐like cells promoted prostate cancer metastasis through activation of transforming growth factor (TGF)‐β1, and that CCL2, CCL4 and CCL22 were associated with prostate cancer progression . Upregulation of CCL5, a high‐affinity ligand of CCR5, can increase the aggressive potential of breast cancer cells and increase the invasiveness of prostate cancer cells .…”
Section: Introductionmentioning
confidence: 99%
“…CCL2 was shown to attract macrophages, and these macrophages transform to tumor‐associated macrophages in the tumor microenvironment and contribute to cancer progression . Tumor‐associated macrophages stimulate prostate cancer cells to secrete CCL17 and CCL22, which increase their migration ability via an autocrine mechanism . The expression level of CCR4 (a common receptor of CCL17 and CCL22) was shown to be associated with the expression level of CCR2 in prostate cancer tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The expression level of CCR4 (a common receptor of CCL17 and CCL22) was shown to be associated with the expression level of CCR2 in prostate cancer tissues. In addition, prostate cancer tissues of patients with locally advanced or metastatic cancer show a high expression of CCR4 . In addition, CCL17 and CCL22 were shown to activate regulatory T‐lymphocytes that inhibit the anticancer cell activity of cytotoxic T‐lymphocytes .…”
Section: Discussionmentioning
confidence: 99%
“…Olkhanud et al showed that the process of breast cancer lung metastasis was correlated with CCR4 expression and regulatory T cells. Moreover, CCL17/CCL22‐CCR4 axis played an important role in migration and invasion in prostate cancer . Gastric carcinoma patients with higher CCR4 expression have a significantly poorer prognosis than patients with lower CCR4 expression .…”
Section: Discussionmentioning
confidence: 99%